Roles of cis- and trans-Changes in the Regulatory Evolution of Genes in the Gluconeogenic Pathway in Yeast - Chang, Ya-Wen (Oxford University Press, 2008)
The yeast Saccharomyces cerevisiae proliferates rapidly in glucose-containing media. As glucose is getting depleted, yeast cells enter the transition from fermentative to nonfermentative metabolism, known as the diauxic shift, which is associated with major changes in gene expression. To understand the expression evolution of genes involved in the diauxic shift and in nonfermentative metabolism within species, a laboratory strain (BY), a wild strain (RM), and a clinical isolate (YJM) were used in this study. Our data showed that the RM strain enters into the diauxic shift ∼1 h earlier than the BY strain with an earlier, higher induction of many key transcription factors (TFs) involved in the diauxic shift. Our sequence data revealed sequence variations between BY and RM in both coding and promoter regions of the majority of these TFs. The key TF Cat8p, a zinc-finger cluster protein, is required for the expression of many genes in gluconeogenesis under nonfermentative growth, and its derepression is mediated by deactivation of Mig1p. Our kinetic study of CAT8 expression revealed that CAT8 induction corresponded to the timing of glucose depletion in both BY and RM and CAT8 was induced up to 50- to 90-folds in RM, whereas only 20- to 30-folds in BY. In order to decipher the relative importance of cis- and trans-variations in expression divergence in the gluconeogenic pathway during the diauxic shift, we studied the expression levels of MIG1, CAT8, and their downstream target genes in the cocultures and in the hybrid diploids of BY–RM, BY–YJM, and RM–YJM and in strains with swapped promoters. Our data showed that the differences between BY and RM in the expression of MIG1, the upstream regulator of CAT8, were affected mainly by changes in cis-elements, though also by changes in trans-acting factors, whereas those of CAT8 and its downstream target genes were predominantly affected by changes in trans-acting factors.